Imaging flow cytometry and fluorescence microscopy in assessing radiation response in lymphocytes from umbilical cord blood and cancer patients. Issue 12 (14th June 2021) - Durdik, Matus; Kosik, Pavol; Jakl, Lukas; Kozackova, Maria; Markova, Eva; Vigasova, Katarina; Beresova, Katarina; Jakubikova, Jana; Horvathova, Eva; Zastko, Lucian; Fekete, Marta; Zavacka, Ingrid; et al.
Abstract: DNA double strand breaks (DSB) induced by ionizing radiation (IR) are usually measured using γH2AX/53BP1 DNA repair foci, that is considered to be the most sensitive assay for DSB analysis. While fluorescence microscopy (FM) is the gold standard for this analysis, imaging flow cytometry (IFC) may offer number of advantages such as lack of the fluorescence background, higher number of cells analyzed, and higher sensitivity in detection of DNA damage induced by IR at low doses. Along with appearance of γH2AX foci, the variable fraction of the cells exhibits homogeneously stained γH2AX signal resulting in so‐called γH2AX pan‐staining, which is believed to appear at early stages of apoptosis. Here, we investigated incidence of γH2AX pan‐staining at different time points after irradiation with γ‐rays using IFC and compared the obtained data with the data from FM. Appearance of γH2AX pan‐staining during the apoptotic process was further analyzed by fluorescence‐activated cell sorting (FACS) of cells at different stages of apoptosis and subsequent immunofluorescence analysis. Our results show that IFC was able to reveal dose dependence of pan‐staining, while FM failed to detect all pan‐staining cells. Moreover, we found that γH2AX pan‐staining could be induced by therapeutic, but not low doses of γ‐rays and correlate well with percentage of apoptotic cells was analyzed using flow cytometric Annexin‐V/7‐AAD assay. Further investigations showed that γH2AX pan‐staining is formed in the early phases of apoptosis and remains until later stages of apoptotic process. Apoptotic DNA fragmentation as detected with comet assay using FM correlated with the percentage of live and late apoptotic/necrotic cells as analyzed by flow cytometry. Lastly, we successfully tested IFC for detection of γH2AX pan‐staining and γH2AX/53BP1 DNA repair foci in lymphocyte of breast cancer patients after radiotherapy, which may be useful for assessing individual radiosensitivity in a clinically relevant cohort of patients.